Inequality of Opportunity and Income Redistribution - Marcel Preuss; Germán Reyes; Jason Somerville; Joy Wu (Institute of Labor Economics (IZA), 2024)
Support for redistribution depends on whether inequality stems from differences in performance or luck, but different sources of luck may impact redistribution differentially. We elicit redistribution decisions from a U.S.-representative sample who observe worker earnings and whether luck influenced their earnings directly ("lucky outcomes") or indirectly by providing a relative advantage ("lucky opportunities"). Participants redistribute less under lucky opportunities. When assessing the impact of unequal opportunities, individuals rely on a heuristic that leads them to underestimate how even a small relative advantage can substantially influence worker earnings. Our findings highlight the role of inferential challenges in shaping attitudes towards inequality.
Keywords: C91; D63; 330; unequal opportunities; inequality; redistribution; luck